Network administration course using ancient techniques and modern means - Linares Alvaro, Manuel José; López Presmanes, Jorge Luis; Sánchez Parrales, Ligia Vanessa; Zambrano Zambrano, Marcos Tulio; Rincón Soto, Idana Beroska (Salud, Ciencia y Tecnología - Serie de Conferencias, 2023)
Foreign Debt, Foreign Direct Investment, financial variablesEducational modalities based on any form of e-learning are becoming increasingly relevant in today’s society, since, on the one hand, and from an economic point of view, they are within the reach of millions of people on the planet, and on the other hand, they eliminate the space-time barriers that any type of course or teaching activity implies; However, there are still subjects and courses that are eminently practical, and their proper learning traditionally involves attendance, accompanied by the traditional practical activities with equipment and devices essential to complete their proper learning. The idea of dictating a completely distance course on network administration and services, a subject with the characteristics described above, aimed at professionals in the field from different universities and centers attached to the Ministry of Higher Education (MES) of Cuba, arises in response to the need to improve the level of preparation of new specialists who are engaged in the activity described; and the novelty of this experience lies in the use of a virtual platform that contains networks and IT devices (routers, switches, etc.), so that each student of the course is able to learn the basics of network administration and network services in a way that each student of the course has the opportunity to learn the basics of network administration and network services. ), so that each student in the course can have his or her own network devices, thus conditioning in a suitable way and with fewer economic resources, the acquisition of the practical skills that this science demands. We conclude by highlighting the high level of satisfaction, learning and skills acquired by the students, and we recommend the transformation of the course into a distance diploma course, aimed at anyone who wants to work as a network administrator in any of the entities attached to the MES.